1968
DOI: 10.1039/j39680002560
|View full text |Cite
|
Sign up to set email alerts
|

Studies in mycological chemistry. Part XXIII. The structure of flavomannin, a metabolite of Penicillium wortmanni Klöck

Abstract: dim et hy I -2,Z'b ia n t h race n e-8 (7H) ,8' (7'H)d i o n e ( XI1 Ia) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
4
6
0
Order By: Relevance
“…28 It was recently discovered by Bara et al that the Talaromyces wortmannii fungus, an endosymbiont of Egyptian Aloe vera (Asphodeloideae), contained several bioactive atropisomeric compounds; and the group conducted extensive studies to determine any potential medicinal application. 29 Analysis of the isolated products 26 found that they were similar to that of previously-reported avomannin, 30 allowing for general structural assignment (Fig. 5, Compounds 11 and 12).…”
Section: Flavomannins and Talaromannins: Potential Novel Route For An...supporting
confidence: 74%
See 3 more Smart Citations
“…28 It was recently discovered by Bara et al that the Talaromyces wortmannii fungus, an endosymbiont of Egyptian Aloe vera (Asphodeloideae), contained several bioactive atropisomeric compounds; and the group conducted extensive studies to determine any potential medicinal application. 29 Analysis of the isolated products 26 found that they were similar to that of previously-reported avomannin, 30 allowing for general structural assignment (Fig. 5, Compounds 11 and 12).…”
Section: Flavomannins and Talaromannins: Potential Novel Route For An...supporting
confidence: 74%
“…Further analysis indicated these were heterodimers composed of one atrochrysone unit, and one unit of either an ether derivative of atrochrysone, named flavomannins C and D ( ECD analysis of the compounds resulted in three pairs of almost mirror-image spectra, suggesting they are atropdiastereomers. Given that the [α] D of one of the compounds matched the value previously reported for flavomannin A (11), 30 the corresponding compound was thought to be its atropdiastereomer, and dubbed flavomannin B (12). Using TD-DFT (B3LYP, BH&HLYP, PBE0/TZVP) ECD calculation protocols, the simulated ECD spectra of both atropisomeric configurations matched well with the experimental ECD data, assuming identical point chirality at C3/C3ʹ.…”
Section: Flavomannins and Talaromannins: Potential Novel Route For Ansupporting
confidence: 74%
See 2 more Smart Citations
“…On the other hand, mitorubrin ( 2 ), mitorubrinol ( 3 ), and mitorubrinol acetate ( 5 ) were isolated as yellow pigments on the ascomata of T. emodensis , T. hachijoensis , and T. wortmannii var. sublevisporus , along with duclauxin from the former fungus, FDM from the middle, and flavomanin from the latter. The optical rotation of mitorubrin derivatives from the three above fungi were all positive (Table ).…”
mentioning
confidence: 97%